A compact CPW-fed wideband metamaterial-inspired antenna for GSM, WLAN/Wi-Fi, and WiMAX applications. Issue 3 (4th April 2016) - Gupta, Ashish; Chaudhary, Raghvendra Kumar
Abstract : A compact coplanar waveguide (CPW)-fed wideband metamaterial-inspired antenna is designed and developed in this paper. The proposed structure is an asymmetric structure in which three rectangular stubs are employed between signal patch and CPW ground plane. It is demonstrated that these stubs provides lumped parameters of conventional epsilon-negative transmission line (ENG-TL). As an advantage of these stubs proposed antenna operates on 1.67–2.76 GHz with −10 dB impedance bandwidth of 49.2%. The proposed antenna having small electrical size of 0.17λ0 × 0.35λ0 × 0.01λ0 at fo = 2.21 GHz. The simulated average gain and radiation efficiency of the proposed antenna is 1.61 dB and 96.33% respectively throughout the bandwidth. Properties such as smaller electrical size, simpler design, consistent radiation characteristics, and ease of fabrication are making this antenna suitable for GSM, WLAN/Wi-Fi, Bluetooth, and WiMAX applications.